2020
DOI: 10.3389/fnbeh.2020.00138
|View full text |Cite
|
Sign up to set email alerts
|

Bolder and Brighter? Exploring Correlations Between Personality and Cognitive Abilities Among Individuals Within a Population of Wild Zebrafish, Danio rerio

Abstract: Within populations, individual differences in behavioral and cognitive traits are dependent on the habitat and specific contexts, such as the presence of a predator or other risks. The ability to show variable responses to changing conditions can be of immense survival advantage to organisms. We studied individual differences in specific personality traits, such as boldness, exploration, and spatial ability, and the effect of these traits on learning ability and memory in the presence of a predatory threat, am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“…‘Boldness’ is usually associated with assertiveness, exploratory activity, risk-taking, and interest in novel environments, objects, and individuals, whereas ‘shyness’ tends to be associated with cautiousness, timidity, and fear of novelty. Male dogs are generally bolder than females [ 76 , 77 ], and boldness can have an effect on various behavioral and cognitive traits in dogs and other species [ 78 , 79 , 80 , 81 ]. According to several studies, female dogs are also more likely to be fearful or anxious than males [ 29 ], and anxiety and stress might also affect performance in cognitive tasks [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…‘Boldness’ is usually associated with assertiveness, exploratory activity, risk-taking, and interest in novel environments, objects, and individuals, whereas ‘shyness’ tends to be associated with cautiousness, timidity, and fear of novelty. Male dogs are generally bolder than females [ 76 , 77 ], and boldness can have an effect on various behavioral and cognitive traits in dogs and other species [ 78 , 79 , 80 , 81 ]. According to several studies, female dogs are also more likely to be fearful or anxious than males [ 29 ], and anxiety and stress might also affect performance in cognitive tasks [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on chimpanzees, capuchins, and zebra finches have shown that there are sex differences in personality (Buirski et al, 1978;Schuett and Dall, 2009;Manson and Perry, 2013). These differences would increase the overall variability in behavior across the species, since males and females are inherently different from each other, as was also shown in a previous study (Daniel and Bhat, 2020). However, studies have also indicated that not all species or populations differ in personality across sexes (Budaev, 1999;Harrison et al, 2021).…”
Section: Discussionmentioning
confidence: 60%
“…Although repeated testing is required to study consistency over time for all behaviors, most studies do not take habituation or improvement in task performance into account. Our previous study that explored the relationship between personality and cognition in wild-caught zebrafish discovered correlations between the two but did not test for consistency in behavior over repeated trials (Daniel and Bhat, 2020).…”
Section: Introductionmentioning
confidence: 96%
“…CB hypothesis suggests that the individuals with larger brains have better cognitive abilities to cope with different changes in the environment, thereby improving their survival rate (Sol, 2009, van der Bijl et al, 2015, Gu et al, 2017. Additionally, in the study of cognitive abilities, most research focuses on the study of learning and memory abilities (Kotrschal and Taborsky, 2010, Baker and Wong, 2019, Silveira et al, 2019, Daniel and Bhat, 2020. Both learning and memory can improve individual survival (Kaneko et al, 2019, Silveira et al, 2019.…”
Section: Introductionmentioning
confidence: 99%